Polymer Nanoformulation of Sorafenib and All-Trans Retinoic Acid for Synergistic Inhibition of Thyroid Cancer - Li, Shijie; Dong, Shujun; Xu, Weiguo; Jiang, Yang; Li, Zhongmin (Frontiers in Pharmacology, 2020)
Part of differentiated thyroid cancer will relapse or develop into dedifferentiated thyroid cancer after standard therapy, such as surgery or radionuclide therapy. Sorafenib (SOR) is recommended for the treatment of advanced or radioiodine-refractory thyroid cancer. The monotherapy using SOR is often hampered by its modest efficacy, serve systemic toxicity, and high occurrence of drug resistance. In order to enhance the antitumor effect of SOR and reduce its side effects, SOR and all-trans retinoic acid (ATRA), a differentiation-promoting drug, were loaded into poly(ethylene glycol)–poly(lactide-co-glycolide) (PEG–PLGA) polymer micelles in this study. The drug-loaded micelles, PM/(SOR+ATRA), exhibited relatively slow drug release and effective cell uptake. Compared with other treatment groups, the PM/(SOR+ATRA) treatment group showed the most significant antitumor effect and minimal systemic toxicity toward the FTC-133 thyroid cancer-bearing BALB/c nude mouse model. Immunohistochemical analysis confirmed that PM/(SOR+ATRA) could significantly promote apoptosis and re-differentiation of tumor cells. All the results demonstrated that polymer micelles loaded with SOR and ATRA could treat thyroid cancer more effectively and safely.